Study on temperature gradient of ultra-thick foam sandwich composite structure during curing - Yi Sun; Xue-Ying Zhao; Yu-Kui Wang; Hai-Tao Zhao; Si-Si Xu; Pei-Zhi Li; Xiao-Chu Gao (Case Studies in Thermal Engineering)
This paper conducts numerical simulations and experimental measurements on the temperature distribution of ultra-thick foam sandwich composite structure with varying ply thicknesses, aiming to investigate the influence of prepreg ply thickness on the temperature gradient of foam sandwich structure. Firstly, the curing kinetic of CYCOM970/T300 prepreg was studied using non-isothermal differential scanning calorimetry (DSC). Then, thermal analysis of foam sandwich composite structure with different ply thicknesses was conducted using ABAQUS software combined with user subroutines. Subsequently, thermocouple sensors were used to measure the curing temperature of foam sandwich structure. The results indicate that the prepreg ply thickness has a significant impact on the temperature gradient during the curing process of foam sandwich structure. When there are a larger number of prepreg plies, overheating of the prepreg on the foam upper layer occurs, resulting in a significant temperature gradient in the thickness direction of the structure. In this case, reducing the heating rate of the autoclave curing process can effectively reduce the temperature overshoot of the prepreg on the foam upper layer.